Self-directed Entrepreneurial Learning - Adri du Toit; Sukie van Zyl; Aubrey Golightly; Thomas Howard Morris; Danél Kruger; Thea Tselepis; Chris Schachtebeck; Cecile Nieuwenhuizen; Faren McCarthy-Kettledas; Gideon P van Tonder; Viné Petzer; Christelle Kruger; et al. (AOSIS, 2025)
The rapid pace of global change challenges education at all levels to prepare 21st‑century learners for a volatile, uncertain, complex and ambiguous (VUCA) world. Self‑directed entrepreneurial learning examines how self‑directed learning (SDL) and entrepreneurial learning (EL) can be integrated across various educational contexts to support lifelong learning, teacher preparation and student adaptability. Beginning with problem‑based entrepreneurial learning (PBEL), this scholarly book explores strategies for fostering self‑directed entrepreneurial learning (SDEL). The authors present empirical studies that illustrate SDL and EL integration across subjects such as Technology, Computer Applications Technology, Economic and Management Sciences, Coding and Robotics, Life Orientation, Life Skills and the arts. Furthermore, the authors investigate approaches such as cooperative learning, productive failure and arts-based project-based learning that offer practical ways to develop these competencies in pre‑service and in‑service teachers. While the studies have been conducted in South Africa, the insights and frameworks brought forward are broadly applicable across the African continent and the Global South. This scholarly volume offers actionable strategies for academics to design, implement and evaluate SDEL, promoting autonomy, entrepreneurial thinking and socially impactful learning in a rapidly changing world.